2022
DOI: 10.3390/antiox11050860
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Biological Activity of the Ethanolic Extract from the Roots of Cannabis sativa L. Grown in Aeroponics

Abstract: Cannabis sativa var. Kompolti, a variety routinely used for food production purposes, is characterized by a low concentration of psychoactive molecules, although containing many other biologically attractive metabolites in all parts of the plant, including the roots. In the present work, we evaluate the specific biological activities of the roots’ extract from plants cultivated through aeroponics, an affordable and reliable method facilitating the isolation and processing of roots, with the advantage of being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The gastro properties of EFCS could be related to several compounds. Indeed, various secondary metabolites have been identified in the ethanolic fractions of C. sativa, the most relevant being the cannabinoids, flavonoids, phytosterols, and terpenes (31,40,41). Previous studies have shown that flavonoids contribute to gastrointestinal protection against ulcers caused by Helicobacter pylori (42), and that cannabinoids protect the gastric mucosa against ethanol and stress-induced damage (43).…”
Section: Discussionmentioning
confidence: 99%
“…The gastro properties of EFCS could be related to several compounds. Indeed, various secondary metabolites have been identified in the ethanolic fractions of C. sativa, the most relevant being the cannabinoids, flavonoids, phytosterols, and terpenes (31,40,41). Previous studies have shown that flavonoids contribute to gastrointestinal protection against ulcers caused by Helicobacter pylori (42), and that cannabinoids protect the gastric mucosa against ethanol and stress-induced damage (43).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that antioxidants, which neutralize harmful free radicals, may have curative effects on conditions such as cardiovascular disease (Zhou et al, 2021), inflammatory illness (Ferrini et al, 2022), cancer, and aging (Dhalaria et al, 2020). DPPH and reducing power were utilized to test the radical scavenging capability of antioxidant activities exhibited by the two compounds at the concentration of 100 µM illustrated in Figure 9 were similar to that of ascorbic acid/vitamin C (the standard drug).…”
Section: Antioxidant Activity Of Friedelin and ((E)−4-(4-hydroxy-3-me...mentioning
confidence: 99%
“…In recent years, there has been increasing interest in examining the pharmacological activities of C. sativa root extracts and their metabolites (Ferrini et al 2022),, including for possible anti-in ammatory, antiasthmatic, antinociceptive, antipyretic, anti-asthmatic, spasmolytic, and antioxidant properties (Ryz et Friedelin is considered a potential resource for dietary supplements (Gao et al 2022) and also displayed natural anti-insecticidal activity for agricultural pests (Baskar et al 2014). Chemical synthesis of these bioactive secondary metabolites is impractical (Guo et al 2020;2022).…”
Section: Introductionmentioning
confidence: 99%